Rancang Bangun Sistem Informasi Pembelian Dan Penjualan Pakaian Pada Toko Al-Gaza Busana Pontianak Berbasis Web - Diaz Arizona, Nanda; Iqbal, Muhammad; Rifani Ihsan, Muhammad Ifan; Sony Maulana, Muhammad; Nurdiani, Siti (LPPM Universitas Bina Sarana Informatika, 2024)
Al-Gaza Busana Store Pontianak is a trading store that sells various clothes ranging from children to adults. The case reviewed in this Final Project is the recording of clothing purchases and sales. Each recording of clothing sales transactions at Al-Gaza Busana Store is still done in a simple way that is recorded in the journal and recording every day and then recorded every once a month. As for the recording of clothing purchases there is no book keeping, just a note of every purchase transaction kept by the shop owner. By looking at the above problem, it is necessary to purchase and sale application at Al-Gaza Busana Store Pontianak that manages data of clothing, clothing data, agent data, admin data, entrant data, purchase transaction, retail sale transaction, wholesale sale transaction. For outputs generated from this application include purchase reports, retail sales reports, and wholesale sales reports. With the application of purchase and sale of clothing processed by the admin, is expected to facilitate in managing the recording of the purchase and sale of clothing more effectively and efficiently.